A debit card is similar to a check because they are both taking money out of a bank account under your name.
Answer:
90 degrees
Step-by-step explanation:
BCO = 66
The whole ABC is 180
So BCO and BDO = 90
Therefore BAO must = 90 degrees
The measures of the four angles of quadrilateral ABCD are 36°, 72°, 108° and 144°
<u>Explanation:</u>
A polygon has three or more sides.
Example:
Triangle has 3 sides
Square has 4 sides
Pentagon has 5 sides and so on.
27)
In a quadrilateral ABCD, the measure of ZA, ZB, ZC and ZD are the ratio 1 : 2 : 3 : 4
We know,
sum of all the interior angles of a quadrilateral is 360°
So,
x + 2x + 3x + 4x = 360°
10x = 360°
x = 36°
Thus, the measure of four angles would be:
x = 36°
2x = 2 X 36° = 72°
3x = 3 X 36° = 108°
4x = 4 X 36° = 144°
Therefore, the measures of the four angles of quadrilateral ABCD are 36°, 72°, 108° and 144°
ANSWER
![( \frac{2}{3} , \frac{1}{5} )](https://tex.z-dn.net/?f=%28%20%5Cfrac%7B2%7D%7B3%7D%20%2C%20%5Cfrac%7B1%7D%7B5%7D%20%29)
EXPLANATION
The first equation is
![\frac{1}{2} x - \frac{3}{4} y = \frac{11}{60} ...(1)](https://tex.z-dn.net/?f=%20%5Cfrac%7B1%7D%7B2%7D%20x%20-%20%20%5Cfrac%7B3%7D%7B4%7D%20y%20%3D%20%20%5Cfrac%7B11%7D%7B60%7D%20...%281%29)
The second equation is
![\frac{2}{5} x + \frac{1}{6} y = \frac{3}{10} ...(2)](https://tex.z-dn.net/?f=%20%5Cfrac%7B2%7D%7B5%7D%20x%20%20%2B%20%20%5Cfrac%7B1%7D%7B6%7D%20y%20%3D%20%20%5Cfrac%7B3%7D%7B10%7D%20...%282%29)
We want to eliminate y, so we multiply the first equation by
![\frac{4}{5}](https://tex.z-dn.net/?f=%20%5Cfrac%7B4%7D%7B5%7D%20)
![\frac{4}{5} \times \frac{1}{2} x - \frac{4}{5} \times \frac{3}{4} y = \frac{11}{60} \times \frac{4}{5}](https://tex.z-dn.net/?f=%20%5Cfrac%7B4%7D%7B5%7D%20%20%5Ctimes%20%5Cfrac%7B1%7D%7B2%7D%20x%20-%20%5Cfrac%7B4%7D%7B5%7D%20%20%20%20%5Ctimes%20%5Cfrac%7B3%7D%7B4%7D%20y%20%3D%20%20%5Cfrac%7B11%7D%7B60%7D%20%20%5Ctimes%20%20%5Cfrac%7B4%7D%7B5%7D%20)
![\frac{2}{5} x - \frac{3}{5} y = \frac{11}{75} ...(3)](https://tex.z-dn.net/?f=%5Cfrac%7B2%7D%7B5%7D%20x%20-%20%5Cfrac%7B3%7D%7B5%7D%20y%20%3D%20%20%5Cfrac%7B11%7D%7B75%7D%20...%283%29)
We now subtract equation (3) from (2)
![(\frac{2}{3} x - \frac{2}{3} x )+ ( \frac{1}{6} y - - \frac{3}{5}y ) =( \frac{3}{10} - \frac{11}{75} )](https://tex.z-dn.net/?f=%20%28%5Cfrac%7B2%7D%7B3%7D%20x%20%20-%20%20%5Cfrac%7B2%7D%7B3%7D%20x%20%29%2B%20%28%20%5Cfrac%7B1%7D%7B6%7D%20y%20-%20%20-%20%20%5Cfrac%7B3%7D%7B5%7Dy%20%29%20%3D%28%20%20%5Cfrac%7B3%7D%7B10%7D%20%20-%20%20%5Cfrac%7B11%7D%7B75%7D%20%29)
![\frac{1}{6} y + \frac{3}{5}y =\frac{3}{10} - \frac{11}{75}](https://tex.z-dn.net/?f=%20%5Cfrac%7B1%7D%7B6%7D%20y%20%20%2B%20%20%5Cfrac%7B3%7D%7B5%7Dy%20%20%3D%5Cfrac%7B3%7D%7B10%7D%20%20-%20%20%5Cfrac%7B11%7D%7B75%7D%20)
![\frac{23}{30}y = \frac{23}{150}](https://tex.z-dn.net/?f=%20%5Cfrac%7B23%7D%7B30%7Dy%20%3D%20%20%5Cfrac%7B23%7D%7B150%7D%20)
Multiply both sides by
![\frac{30}{23}](https://tex.z-dn.net/?f=%20%5Cfrac%7B30%7D%7B23%7D%20)
![\implies \: \frac{30}{23} \times \frac{23}{30}y= \frac{23}{150} \times \frac{30}{23}](https://tex.z-dn.net/?f=%20%20%5Cimplies%20%5C%3A%20%20%5Cfrac%7B30%7D%7B23%7D%20%5Ctimes%20%20%5Cfrac%7B23%7D%7B30%7Dy%3D%20%20%5Cfrac%7B23%7D%7B150%7D%20%20%5Ctimes%20%20%5Cfrac%7B30%7D%7B23%7D)
![\implies \: y = \frac{1}{5}](https://tex.z-dn.net/?f=%20%5Cimplies%20%5C%3A%20y%20%3D%20%20%5Cfrac%7B1%7D%7B5%7D%20)
Substitute into the first equation to solve for x .
![\frac{1}{2} x - \frac{3}{4} \times \frac{1}{5} = \frac{11}{60}](https://tex.z-dn.net/?f=%5Cfrac%7B1%7D%7B2%7D%20x%20-%20%20%5Cfrac%7B3%7D%7B4%7D%20%20%5Ctimes%20%5Cfrac%7B1%7D%7B5%7D%20%3D%20%20%5Cfrac%7B11%7D%7B60%7D)
Multiply to obtain
![\frac{1}{2} x - \frac{3}{20} = \frac{11}{60}](https://tex.z-dn.net/?f=%5Cfrac%7B1%7D%7B2%7D%20x%20-%20%20%5Cfrac%7B3%7D%7B20%7D%20%3D%20%20%5Cfrac%7B11%7D%7B60%7D)
![\frac{1}{2} x = \frac{11}{60} + \frac{3}{20}](https://tex.z-dn.net/?f=%5Cfrac%7B1%7D%7B2%7D%20x%20%3D%20%5Cfrac%7B11%7D%7B60%7D%20%2B%20%5Cfrac%7B3%7D%7B20%7D)
![\frac{1}{2} x = \frac{1}{3}](https://tex.z-dn.net/?f=%5Cfrac%7B1%7D%7B2%7D%20x%20%3D%20%5Cfrac%7B1%7D%7B3%7D%20)
Multiply both sides by 2.
![2 \times \frac{1}{2} x =2 \times \frac{1}{3}](https://tex.z-dn.net/?f=2%20%5Ctimes%20%5Cfrac%7B1%7D%7B2%7D%20x%20%3D2%20%5Ctimes%20%20%5Cfrac%7B1%7D%7B3%7D%20)
![x = \frac{2}{3}](https://tex.z-dn.net/?f=x%20%3D%20%5Cfrac%7B2%7D%7B3%7D%20)
The solution is
![( \frac{2}{3} , \frac{1}{5} )](https://tex.z-dn.net/?f=%28%20%5Cfrac%7B2%7D%7B3%7D%20%2C%20%5Cfrac%7B1%7D%7B5%7D%20%29)